The efficacy and adverse effects of nivolumab and lenvatinib in the treatment of advanced hepatocellular carcinoma: Nivolumab and lenvatinib in the treatment of HCC - Wen, Shilai; Zeng, Jingke; Zhong, Liting; Ye, Jianmin; Lai, Xiaohuan (Cellular and Molecular Biology, 2022)
This study intends to investigate nivolumab’s efficacy and adverse effects in combination with lenvatinib in treating advanced hepatocellular carcinoma (HCC). For this purpose, ninety-two patients with unresectable advanced HCC admitted were enrolled and were divided into the control group (N=46) and the observation group (N=46) according to the random number table. The control group was treated with lenvatinib while the observation group was treated with nivolumab combined with lenvatinib. The efficacy, adverse effects, liver function, completion rate, interruption and discontinuation of treatment, drug reduction, serum tumor markers, and immune function were compared between the two groups. Also, changes in the expression of some genes that regulate the cell cycle (P53, RB1, Cyclin-D1, c-fos, and N-ras) were investigated in the development of this cancer. According to the results, ORR and DCR (45.65%, 78.26%) in the observation group were higher than those (23.91%, 54.35%) in the control group (P<0.05); The incidence of adverse reactions in the observation group was slightly higher than that of the control group, but the difference was not significant (P>0.05); The rate of completion, interruption, discontinuation of treatment and drug reduction did not differ significantly between two groups (P>0.05); After treatment, the serum ALT, AST, TBIL, and GGT levels decreased and were lower in observation group than in control group (P<0.05); The serum tumor markers AFP, ENO1, GPC3, CEA levels decreased in both groups after treatment, and were lower in the observation group than in control group (P<0.05); CD3, CD4, CD8, and NK levels were improved in the observation group and worsened in the control group, and CD3, CD4, and NK levels were higher in the observation group and lower in the control group after treatment (P<0.05). All in all, nivolumab combined with lenvatinib for advanced hepatocellular carcinoma can improve tumor control, reduce tumor load, and improve liver function and immune function. Common adverse reactions include fatigue, loss of appetite, elevated blood pressure, hand-foot skin reaction, diarrhea, and rash, which should be controlled during treatment.